On the transposability of change management research results: a systematic scoping review of studies published in JOCM and JCM. Issue 5 (1st July 2020) - Lauzier, Martin; Lemieux, Nathalie; Montreuil, Véra-Line; Nicolas, Caroline
Abstract : Purpose: The purpose of this study was to assess the transposability of study results published in the Journal of Organizational Change Management (JOCM) and the Journal of Change Management (JCM) between 2000 and 2019 for change-management practitioners and researchers. Design/methodology/approach: A systematic scoping review of a large sample of articles published in both journals was undertaken: 122 studies were considered for analysis and coded by two independent coders using an inductive grid. Findings: Findings show that few studies (1) describe the nature of changes undertaken by organizations; (2) explain the contextual elements that characterize the environment at the moment when these same transformations are deployed; or (3) nuance their observations according to the change operation. Research limitations/implications: Information on the type of change undertaken by the organization and about how change has been implemented is useful when communicating new scientific knowledge to practitioners. Nevertheless, the way in which studies are sometimes described masks some important nuances to be considered when interpreting or replicating certain results. Practical implications: The relevance of these issues is enhanced by the fact that researchers or practitioners (as knowledge users) are likely to reproduce some of the actions carried out in previous studies in order to deepen research avenues or to facilitate the implementation of change initiatives in workplaces. Originality/value: This research is among the first to assess the transferability of change-management study results published in both journals over such a long period. Its relevance also speaks to the importance of contextualizing results to ease their transposability by researchers and practitioners.